SYNTHESIS, COMPUTER AIDED SCREENING AND PHARMACOLOGICAL EVALUATION OF 2/3-SUBSTITUTED-6(4-METHYLPHENYL)-4,5-DIHYDROPYRIDAZIN3(2H)-ONES, AND PYRIDAZINE SUBSTITUTED TRIAZINE - Khokra, Sukhbir Lal; Seth, Sonakshi; Garg, Shama S; Kaushik, Pawan; Ahmad, Aftab; Khan, Shah Alam; Husain4, Asif (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2015)
The present research work involved synthesis of some new pyridazine derivatives and evaluation of their analgesic and anti-inflammatory activities in experimental animals to obtain safer non-steroidal anti-inflammatory agents (NSAIDs). Friedel-Crafts acylation reaction of succinic anhydride with toluene in the presence of anhydrous aluminum chloride gave 4-(4-methylphenyl)-4-oxo-butanoic acid (1). The aryl propionic acid 1 on reaction with phenyl hydrazine and hydrazine hydrate yielded the pyridazinone derivative 2 and 3, respectively. Reaction of the compound 3 with phosphorus oxychloride (POCl3) produced the corresponding chloropyridazine derivative 4. A 4-hydroxymethyl derivative of dihydropyridazinone (5) was synthesized by condensing 3 with methanol and formaldehyde (HCHO). The compound 5 on further treatment with guanidine hydrochloride in ethanol gave the pyridazino-triazine (6). The synthesized compounds were investigated for their analgesic activity in mice and anti-inflammatory activity in Wistar albino rats. The molecular, pharmacokinetic and toxicity properties of the synthesized compounds were calculated by Molinspiration and Osiris property explorer software. The results of in-vivo anti-inflammatory studies revealed that the compound. 4 showed maximum inhibition in paw edema volume followed by compound 3 while the compound 4 exhibited excellentÂ peripheral analgesic activity (74%) followed by the compound 5. Compound s 4 and 5 also showed good central analgesic effect increased the reaction time to 90 minutes. All the title compounds except compound 5 are predicted to be safe by Osiris online software and are likely to have good oral bioavailability as they obey Lipinskiâs rule of five for drug likeness.Keywords:Â Pyridazinone, Hydrazine derivatives, Chloropyridazine, Triazin-2-imine.